Exploring the relationship between takeover market and enterprise innovation: The mediating role of internal governance - Zheng Li; Chaohui Xu; Haikuan Zhang; Samma Faiz Rasool; Zeeshan Fareed (Journal of Innovation & Knowledge (JIK), 2022)
This study explores the relationship between the takeover market and enterprise innovation. We also investigate the mediating role of internal governance (managers' compensation incentives, equity incentives, boards of directors, and large shareholders) on the relationship between the takeover market and enterprise innovation. We use comprehensive panel data of 1307 firms listed on the Shenzhen and Shanghai stock exchanges for 2006-2016 to meet the study's objectives. We find that the takeover market positively and significantly influences corporate innovation. It improves corporate innovation ability by increasing managers' compensation incentives. However, enterprise innovation ability decreases with an increase in managers' equity incentives, large shareholders, and the board of directors. Finally, this study recommends useful policy implications to increase enterprise innovation in the Chinese financial market.
Keywords: 650; Chinese stock market; Enterprise innovation; Internal governance; Takeover market